2021
DOI: 10.1080/13691058.2020.1849802
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent girls’ perceived readiness for sex in Central Uganda - liminal transitions and implications for sexual and reproductive health interventions

Abstract: Young women in Uganda are at risk of negative sexual and reproductive health outcomes, in part because of sex with older men. Theoretically grounded in the concept of liminality, this paper examines perceived markers of adolescent girls' suitability for sexual activity. In 2014, we conducted 19 focus group discussions and 44 in-depth interviews in two communities in Uganda. Interviews were conducted using a semi-structured tool, audiorecorded and transcribed verbatim. Interviews examined markers of transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Findings from formative research by the Learning Initiative on Norms, Exploitation and Abuse (LINEA) 1 in Brazil, Tanzania and Uganda show that for adolescent girls and young women the social norms driving their participation in transactional sex include community expectations that they should receive money, gifts or other benefits from sexual partners, that if they receive gifts they are expected to reciprocate sexually, and that they gain social status through ownership of material items (acquired through these relationships). For men, social norms driving participation in transactional sex include community expectations that men provide financially in sexual relationships, and that men should have a heightened sexuality and sexual prowess (8)(9)(10)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Findings from formative research by the Learning Initiative on Norms, Exploitation and Abuse (LINEA) 1 in Brazil, Tanzania and Uganda show that for adolescent girls and young women the social norms driving their participation in transactional sex include community expectations that they should receive money, gifts or other benefits from sexual partners, that if they receive gifts they are expected to reciprocate sexually, and that they gain social status through ownership of material items (acquired through these relationships). For men, social norms driving participation in transactional sex include community expectations that men provide financially in sexual relationships, and that men should have a heightened sexuality and sexual prowess (8)(9)(10)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…We collected data to explore beliefs about whether ADTS is exploitative and social norms upholding the practice. The research was conducted in partnership with local research institutions in Tanzania, Uganda, and Brazil from 2016 to 17, and the methods and findings from the research in all three contexts have been reported elsewhere ( Wamoyi et al, 2018 , 2019 ; Howard-Merrill et al, 2020 ; Ignacio et al, 2020 ; Kyegombe et al, 2020a , b , c ; Wamoyi et al, 2021 ; Perrin et al, 2022 ). Following this qualitative formative research phase we chose to conduct the LINEA Intervention development process in Tanzania.…”
Section: Linea Intervention Development Research: Key Aims and Methodsmentioning
confidence: 99%
“…We define ADTS as transactional sex occurring between adolescent girls under the age of 18 and adult men more than 10 years older. Negative consequences of ADTS for adolescent girls include: increased risk of HIV and sexually transmitted infections (STIs); unplanned pregnancy; abortion; child marriage; school dropout; social sanctions; intimate partner violence; and sexual coercion ( Luke and Kurz, 2002 ; Tener, 2019 ; Muthoni et al, 2020 ; UNAIDS, 2020 ; Kyegombe et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…In‐depth interviews and focus group discussions were conducted in Luganda, audio recorded, translated, and transcribed verbatim into English. See Kyegombe et al, 2021; Kyegombe, Meiksin, Namakula, et al, 2020; Kyegombe, Meiksin, Wamoyi, et al, 2020 for more information on study context and data collection.…”
Section: Methodsmentioning
confidence: 99%
“…Transactional sex is driven by the expectation that men are responsible for material provision and women should reciprocate with sex (Kyegombe, Meiksin, Namakula, et al, 2020). The experiences and meanings ascribed to transactional sex vary (Kyegombe et al, 2021; Kyegombe, Meiksin, Namakula, et al, 2020; Kyegombe, Meiksin, Wamoyi, et al, 2020); but transactional sex between younger women and older men is fundamentally shaped by socioeconomic inequalities, where adolescent girls and young women are at a gendered economic disadvantage (Kyegombe, Meiksin, Wamoyi, et al, 2020). Age‐disparate transactional sex—transactional sex between adolescent girls and men at least 5–10 years older—is associated with early sexual debut, multiple, concurrent sexual partners and unprotected sex, and contributes to early, unplanned pregnancies, STIs including HIV, intimate partner violence, and sexual violence (Wamoyi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%